2009
DOI: 10.2139/ssrn.1437648
|View full text |Cite
|
Sign up to set email alerts
|

The Deterrence Effects of U.S. Merger Policy Instruments

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 45 publications
3
19
0
Order By: Relevance
“…More recently, Baarsma et al () completed a similar survey for the Dutch antitrust authority and confirmed this point regarding the rarity of pro‐competitive mergers being deterred. Additionally, Clougherty and Seldeslachts () find that changes in the tenor of U.S. merger policy affect future horizontal merger activity but do not affect future non‐horizontal merger activity. Since U.S. authorities almost exclusively target horizontal merger activity as potentially anti‐competitive, these results also support the idea that merger control does not deter anti‐competitive mergers.…”
Section: A Deterrence Frameworkmentioning
confidence: 99%
See 4 more Smart Citations
“…More recently, Baarsma et al () completed a similar survey for the Dutch antitrust authority and confirmed this point regarding the rarity of pro‐competitive mergers being deterred. Additionally, Clougherty and Seldeslachts () find that changes in the tenor of U.S. merger policy affect future horizontal merger activity but do not affect future non‐horizontal merger activity. Since U.S. authorities almost exclusively target horizontal merger activity as potentially anti‐competitive, these results also support the idea that merger control does not deter anti‐competitive mergers.…”
Section: A Deterrence Frameworkmentioning
confidence: 99%
“…Second, we can consider whether it is the horizontal and vertical merger activity considered by the EC to be potentially anti‐competitive which is principally deterred by EC merger policy. Akin to the Clougherty and Seldeslachts () setup, this differentiation takes advantage of the fact that EC officials deem certain horizontal and vertical mergers (i.e., non‐conglomerate activity) to be the population within which anti‐competitive mergers can arise, while the EC does not consider conglomerate merger activity—and certain types of horizontal and vertical merger activity—to generally raise competitive issues. We do, however, face the limitation that we can only identify these differences in clearly pro‐competitive and potentially anti‐competitive merger activity for a subset (2000–2009) of our data sample.…”
Section: A Deterrence Frameworkmentioning
confidence: 99%
See 3 more Smart Citations